Daendels's self-tempered ambitions. An architectural analysis of the Government House in Weltevreden (the present Jakarta) (Bulletin KNOB, 2005)
The Government House in Weltevreden was built in the period 1809-1827 in Batavia, 'capital' of the Dutch colony in the East-Indies. Construction was ordered by governor-general H.W. Daendels (1808-1811) and completed by governor-general L.P.J. du Bus de Ghisignies (1826-1830). The building has been preserved and is located at the present Lapangan Banteng, Jakarta Pusat, which in the nineteenth century was known as Paradeplaats and since 1828 as Waterlooplein.At present it houses the Ministry of Finance of Indonesia. As an ambitious governor-general, Daendels stimulated the move southwards from Batavia; the densely populated and unhealthy walled city. The area of Weltevreden, several kilometres south of Batavia, was developed and would turn into a highly fashionable area. The Government House, which had to serve as the new governor's residence, had to be constructed in this new developing area, near military encampments.Surviving ground-plans and other drawings and texts from the beginning of the nineteenth century reveal original construction details. An original design of a grand room with a largely protruding front ressault containing a veranda with two stairs at the sides was not realised. The more subtly constructed veranda was closed after construction, probably in 1826-1827.With its large dimensions, its concept of a main building with two side wings, its concept of two large storeys on top of a storey disguised as a base and its clearly European appearance, the building refers to northwest European palaces or to the Government House of a concurring colony like India.All this was constructed out of the materials from demolished buildings reminiscent of the pre-colonial period of the VOC (East Indian Company), like the Castle, the City walls and the Dutch Church (where Jan Pietersz. Coen, the founder of Batavia, had been buried!). Daendels clearly wanted to mark the start of a new era.